Multidisciplinary approach for hepatocellular carcinoma arising from cirrhotic liver with Budd-Chiari syndrome: a case report - Sangmi Kim; Ji Hoon Kim; Ji Won Han; Jeong Won Jang; Jong Young Choi; Seung Kew Yoon; Pil Soo Sung (Korean Liver Cancer Association, 2022)
Budd-Chiari syndrome (BCS) is defined by the obstruction of the hepatic venous outflow between the small hepatic veins and the junction of the inferior vena cava (IVC) with the right atrium. BCS with IVC obstruction occasionally progresses to hepatocellular carcinoma (HCC). Here, we report the case of a patient with HCC arising from a cirrhotic liver with BCS, in whom the hepatic portion of the IVC was obstructed, and who had a favorable outcome with a multidisciplinary approach and IVC balloon angioplasty.